The Relationship of Timeliness and Price to Consumer Goals in PT. Kalerindo Semesta Abadi - Elisabeth Nainggolan; Selamat; Pesta Gultom (Enrichment : Journal of Management, 2022)
This study aims to determine The Relationship of Timeliness and Price to Consumer Goals in PT. Kalerindo Semesta Abadi. This study uses quantitative data and the data source is secondary data. The unit of analysis and observation in this study is the shop with a total population of 150 shop. From the population selected by the random sampling technique obtained 150 samples. The analytical method used in this research is multiple linear regression with the regression equation for Consumer Goals = 1.812 + 0,419 Relationship of Timeliness + 0,178 Price + e. Researchers also use a significance level of 5%. The results of the partial study show that Relationship of Timeliness has a value of tcount > ttable which is 2.866 > 1.972 and a significant value of <0.05, which is 0.005 < 0.05. Price has a value of tcount > ttable with the value is 6.776 > 1.972 and the significant value < 0.05 which is 0.000 < 0.05. The results of the study simultaneously show that Relationship of Timeliness, Price, and Consumer Goals has , Fcount > Ftable with a value of 50.808 > 3.06 and a significant value < 0.05, which is 0.000 < 0, 05. The coefficient of determination (R Square) is 0.507 or 50.7%, which means that the variable Consumer Goals can be explained by the variable the Relationship of Timeliness and Price. While the remaining 49.3% is the variable Consumer Goals. can be explained by other variables not examined in this study, such as Market Segmentation, Market targeting and Sales Volume.